(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Mangrove ecosystem is one of the coastal ecosystems with a high level of productivity, so its existence can be enrich coastal areas and maintain the balance of ecosystems. This study aims to explain the changes in the extent and distribution of mangrove ecosystems within 20 years, from 2000 to 2020 and to know the condition of mangrove ecosystem vegetation in Tanakeke Island. This research was conducted from January to April 2020 in Tanakeke Island. Determination of research location using purposive sampling method. Analysis of changes in mangrove ecosystem area from 2000 to 2020 using supervised classification method with maximum likelihood analysis, while the condition of mangrove ecosystem vegetation using important value index (INP) analyst method and species diversity index. The results showed that mangrove ecosystems in Tanakeke Island from 2000 to 2020 degraded for about -337.41 ha (28.32% of the area in 2000). At the research site found 9 types of mangroves, such as Bruguiera gymnorrhiza, Ceriops tagal, Rhizophora stylosa, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, Phemphis acidula, Lumnitzera racemosa and Ceriops decandra. Mangrove type Rhizophora mucronata has the highest important value index of 192.55%, while for diversity of species in general is relatively low.